Age-related changes in proprioception of the ankle complex across the lifespan - Yang, Nan (J Sport Health Sci, 2019)
BACKGROUND: Ankle complex proprioceptive ability, needed in active human movement, may change from childhood to elderly adulthood; however, its development across all life stages has remained unexamined. The aim of the present study was to investigate the across-the-lifespan trend for proprioceptive ability of the ankle complex during active ankle inversion movement. METHODS: The right ankles of 118 healthy right-handed participants in 6 groups were assessed: children (6–8 years old), adolescents (13–15 years old), young adults (18–25 years old), middle-aged adults (35–50 years old), old adults (60–74 years old), and very old adults (75–90 years old). While the participants were standing, their ankle complex proprioception was measured using the Active Movement Extent Discrimination Apparatus. RESULTS: There was no significant interaction between the effects of age group and gender on ankle proprioceptive acuity (F (5, 106) = 0.593, p = 0.705, η(2)(p) = 0.027). Simple main effects analysis showed that there was a significant main effect for age group (F (5, 106) = 22.521, p < 0.001, η(2)(p) = 0.515) but no significant main effect for gender (F (1,106) =  2.283, p = 0.134, η(2)(p) = 0.021) between the female (0.723 ± 0.092, mean ± SD) and the male (0.712 ± 0.083) participants. The age-group factor was associated with a significant linear downward trend in scores (F (1, 106) = 10.584, p = 0.002, η(2)(p) = 0.091) and a strong quadratic trend component (F (1,106) = 100.701, p < 0.001, η(2)(p) = 0.480), producing an asymmetric inverted-U function. CONCLUSION: The test method of the Active Movement Extent Discrimination Apparatus is sensitive to age differences in ankle complex proprioception. For proprioception of the ankle complex, young adults had significantly better scores than children, adolescents, old adults, and very old adults. The middle-aged group had levels of ankle proprioceptive acuity similar to those of the young adults. The scores for males and females were not significantly different. Examination of the range of the scores in each age group highlights the possible level that ankle complex movement proprioceptive rehabilitation can reach, especially for those 75–90 years of age.